Perkembangan Penerapan Teknologi Artificial Intelligence di Indonesia - Hanna Kirana Apriliana; Yoke Pribadi Kornarius; Angela Caroline; Triningtyas Elisabeth Putri Gusti; Agus Gunawan (Jurnal Syntax Admiration, 2024)
Different employee backgrounds cause differences in their readiness to use AI. One of the important factors that causes doubts among potential AI users is data security. This research focuses on the application of AI technology in corporate environments in Indonesia, with the aim of understanding the attitudes of potential AI users and the factors that influence their intention to use this technology. This study aims to determine the application of AI technology in daily work from the perspective of prospective AI users. The 100 prospective AI users who were sampled in the study were employees from various levels in several fields of the company. The data processing technique uses regression tests for quantitative data which are complemented by thematic analysis for qualitative data. The results of the regression test show that attitude has a considerable influence on the intention to use AI.